"THE BEAUTY AND RESILIENCE OF KASHMIRI CULTURE AND TRADITIONS: EXPLORING THE UNIQUE PRACTICES AND CUSTOMS OF THE KASHMIRI PEOPLE" - Sarfaraz Ahmad Rather; Dr. R. Rajeshwari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Abstract The culture and traditions of Kashmir are a rich and varied mosaic that has been made over hundreds of years. Located in the northernmost part of India, Kashmir has been influenced by a numerous of cultures and religions, resulting in a unique blend of traditions and practices. The people of Kashmir are known for their warm hospitality, intricate handicrafts, delicious cuisine, and music and dance that reflect their heritage. Despite its beauty and richness, Kashmiri culture has faced challenges such as conflict, displacement, and environmental degradation, Kashmiri culture and traditions have remained resilient and continue to thrive. By exploring the unique practices and customs of the Kashmiri people, this paper aims to highlight the beauty and richness of their cultural heritage and the importance of preserving it for future generations.